„Czyńcie sobie ziemię poddaną” (Rdz 1,28). Cywilizacyjny postęp ludzkości w świetle Rdz 1-11 - Szymik, Stefan (Verbum Vitae, 2017)
The aim of the paper is to explore the advancement of human civilization and the role and impact of human beings, who are to be dominant over animals and subdue the earth. The study is based on the texts of Gen 1–11. First, the author examines Gen 1:26-28 and the two important verbs “have dominion over” and “subdue” in their literary and theological contexts. Created man is an imago Dei and as such has domination over animals and the earth as a representative of God. The next step was to examine the biblical texts which illustrate the progressive, unrestricted growth of the economic and cultural possibilities of humankind (cf. Gen 4:2-4.17-22; 9:1-7, 20-27; 11:1-9). Finally, the author discusses the limitations and restrictions inherent in the progress of human civilization. The extraordinary potential of humankind has its limits, since humanity is only the ambassador of God on earth and thus executes duties in his name, while the earth itself is given to all of mankind and not to any one chosen nation or defined group.